46=17+x

Simple and best practice solution for 46=17+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 46=17+x equation:


Simplifying
46 = 17 + x

Solving
46 = 17 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
46 + -1x = 17 + x + -1x

Combine like terms: x + -1x = 0
46 + -1x = 17 + 0
46 + -1x = 17

Add '-46' to each side of the equation.
46 + -46 + -1x = 17 + -46

Combine like terms: 46 + -46 = 0
0 + -1x = 17 + -46
-1x = 17 + -46

Combine like terms: 17 + -46 = -29
-1x = -29

Divide each side by '-1'.
x = 29

Simplifying
x = 29

See similar equations:

| 3y+3-3y-4=-6 | | 18=2x-24 | | 2y-10=-2 | | 4z-17-z+5=0 | | 3x^2-5x=-x^2+3x+7 | | 0=.5x^2+.5x+1.2 | | x=10.875 | | 5=8x-8 | | 7x+5=90 | | 13=15m+14 | | 3x^2+x=60 | | -p+7(4p-3)+5= | | 5=-7r+2r | | 40x^2+104x+48=0 | | x+133=125 | | 5x-9=4x+11 | | 2x-13+11=x+9 | | X^2-1=2-2x | | x^4-8x^3+14x^2+7x+1=0 | | -3(x-6)=2(5x-4) | | x+15+4x-45= | | 4a+9=9 | | -5c+3=-17 | | -(-3v+u)+3(-3u+v)= | | 2x-18=-40 | | 7.4-9.2=2.6+5.3 | | 8n+2n-6+9=5 | | -10r+12r=-18 | | ax+bx-4=-9 | | 3(x+2)=2x+5 | | 48p+(-32)=16 | | x+15-4x-45= |

Equations solver categories